2000
DOI: 10.1037/0022-0663.92.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of students who enroll and succeed in psychology Web-based classes.

Abstract: This study compared the cognitive-motivational and demographic characteristics of students enrolled in 3 Web-based sections of Psychological Statistics with their counterparts in 3 conventional (face-to-face) sections of this course. No demographic differences were found; however, cyberstudents exhibited a greater external locus of control than conventional students. The authors also investigated whether there were any predictors of student performance in Web courses. Measures of on-line course activity (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
128
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(145 citation statements)
references
References 21 publications
9
128
1
3
Order By: Relevance
“…Adult distance education students have different wants and needs. This conclusion agrees with the research of Grandzol and Grandzol (2010), Kuo et al (2013), Arbaugh and Rau (2007), Wang and Newlin (2000), and Liu (2008).…”
Section: Conclusion and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Adult distance education students have different wants and needs. This conclusion agrees with the research of Grandzol and Grandzol (2010), Kuo et al (2013), Arbaugh and Rau (2007), Wang and Newlin (2000), and Liu (2008).…”
Section: Conclusion and Discussionsupporting
confidence: 82%
“…Wang and Newlin (2000) assert faculty need to know more about the characteristics of students who enroll in distance education classes. Because little is known about these students, Smith (1997) questions whether instructors can effectively design distance education courses for them.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A number of studies have found that only attendance behaviours are correlated with final grades. For example, in higher education Wang and Newlin (2000) looked at homepage hits, posts read, and posts written for 51 students in three sections of a Psychology course. They found that the one frequency behaviour -homepage hits -alone predicted student grades.…”
Section: Prior Research On Online Behavioursmentioning
confidence: 99%
“…However, although online learning at the K-12 level has grown rapidly, research using LMS data at this level remains sparse (Lowes, 2014), especially compared to the amount of work in higher education. In addition, as we will see below, the existing research has looked at different variables and has yielded mixed and sometimes contradictory results (Davies & Graff, 2005;Dawson, McWilliam & Tan, 2008;Hung, Hsu, & Rice, 2012;Hung & Zhang, 2008;Liu & Cavanaugh, 2011a, 2011b, 2012Macfadyen & Dawson, 2010;Ramos & Yudko, 2008;Ryabov, 2012;Wang & Newlin, 2000;Wei, Peng, & Chou, 2015). This paper uses LMS data generated by approximately 700 high school students who were enrolled in 12 asynchronous cohort-paced online courses offered by Pamoja Education (PJE), the course provider for the International Baccalaureate (IB), in order to explore the link between LMS behaviours and course outcomes at the high school level.…”
Section: Introductionmentioning
confidence: 99%
“…Goldberg discusses tracking information in the LMS WebCT [3]. Wang predict student performances early by tracking the data on student online activity in a web-based learning management system (LMS) [4] [5]. More recently, John Campbell proposed that the academic analytics of LMS data can identify students at risk of attrition or course failure [6].…”
Section: Motivationmentioning
confidence: 99%